Impaired right ventricular function in long-term survivors of allogeneic haematopoietic stem-cell transplantation - Lars Gullestad; Anette Borger Kvaslerud; Svend Aakhus; Jan Otto Beitnes; Richard John Massey; Phoi Phoi Diep; Marta Maria Burman; Lorentz Brinch; Ellen Ruud (Open Heart)
Aims Survivors of allogeneic haematopoietic stem-cell transplantation (allo-HSCT) are at higher risk of cardiovascular disease. We aimed to describe right ventricular (RV) systolic function and risk factors for RV dysfunction in long-term survivors of allo-HSCT performed in their youth.Methods and results This cohort included 103 survivors (53% female), aged (mean±SD) 17.6±9.5 years at allo-HSCT, with a follow-up time of 17.2±5.5 years. Anthracyclines were used as first-line therapy for 44.7% of the survivors. The RV was evaluated with echocardiography, and found survivors to have reduced RV function in comparison to a group of healthy control subjects: Tricuspid annular plane systolic excursion, (TAPSE, 20.8±3.7 mm vs 24.6±3.8 mm, p<0.001), RV peak systolic velocity (RV-s’, 11.2±2.3 cm/s vs 12.3±2.3 cm/s, p=0.001), fractional area change (FAC, 41.0±5.2% vs 42.2±5.1%, p=0.047) and RV free-wall strain (RVFWS, −27.1±4.2% vs −28.5±3.3%, p=0.043). RV systolic dysfunction (RVSD) was diagnosed in 14 (13.6%), and was strongly associated with progressive left ventricular systolic dysfunction (LVSD). High dosages of anthracyclines were associated with greater reductions in RV and LV function. Multivariable linear regressions confirmed global longitudinal strain to be a significant independent predictor for reduced RV function.Conclusion Impaired RV function was found in long-term survivors of allo-HSCT who were treated in their youth. This was associated with progressive left ventricle dysfunction, and pretransplant therapies with anthracyclines. The occurrence of RVSD was less frequent and was milder than coexisting LVSD in this cohort.